The Role of Lumbar Sympathectomy in the Management of Buerger's Disease: A Systematic Review - Helin Hussein; Luqman M. Ali Hassan; Piwand Abdulkarim; Suhaib H. Kakamad; Abdullah K. Ghafour; Imad J. Habibullah; Muhammed Bag A. Ali; Dlshad Hamasaeed Ahmed; Deari A. Ismaeil; Omer H.G. Hawramy; Hemn H. Kaka Ali; Hiwa O. Abdullah; et al. (Barw Medical Journal, 2023)
AbstractIntroductionLumbar sympathectomy has been explored to manage Buerger's disease (BD) with varying success rates, but the results are often controversial. Despite the substantial morbidity associated with BD, there is a scarcity of comprehensive reviews on the topic. The current study is a systematic review of the efficacy of lumbar sympathectomy in the management of BD.MethodsA meticulous systematic exploration was conducted across reputable databases and search platforms. The search strategy employed the following keywords:(lumbar sympathetic OR sympathectomy OR lumbar sympathetic block) AND (Buerger's disease OR Buerger OR thromboangiitis obliterans OR lower limb disease). Out of 42 identified studies, 16 were excluded during the initial screening phase. Following initial and full-text screenings, 10 studies remained eligible. The assessment of studies regarding the inclusion criteria was conducted independently by two authors, with a third author intervening to arbitrate any discrepancies.ResultsThe demographic characteristics revealed that all participants were male, with a mean age of 38.9 years. Smoking prevalence among the cases was notably high (99%). Chemical sympathectomy was the predominant intervention, employed in 87.8% of cases, while surgical sympathectomy was utilized in only 12.2% of cases. Among the cases, 8.7% achieved complete resolution from the disease, while 91.3% reported partial relief.ConclusionLumbar sympathectomy can be a viable treatment option for BD with fair outcomes. Nevertheless, smoking cessation remains the primary factor impeding disease progression and aggressiveness.